2016
DOI: 10.3892/mmr.2016.5590
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multidrug-resistant osteosarcoma sublines and the molecular mechanisms of resistance

Abstract: Multidrug resistance (MDR) is a challenge for the treatment of cancer and the underlying molecular mechanisms remain elusive. The current study exposed MG63 osteosarcoma cells to increasing concentrations of vincristine (VCR) to establish four VCR‑resistant MG63/VCR cell sublines (MG63/VCR1, 2, 3 and 4). The drug resistance indices (RI) of these sublines was detected with the CCK‑8 assay and determined to be163, 476, 1,247, and 2,707‑fold higher than that of parental cells, respectively. These sublines also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In the present study, the roles of differentially expressed genes in VCR resistance of osteosarcoma cells were investigated by microarray analysis. Numerous genes determined as differentially expressed in VCR-resistant osteosarcoma cells may also be associated with VCR resistance in the present study, such as MDR1 (11), which was upregulated in MG63/VCR cells. Previous studies have indicated that MDR1 serves a key role in the proliferation and survival of epithelial and malignant cells during tumorigenesis, as well as in acquired drug resistance (15,16).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In the present study, the roles of differentially expressed genes in VCR resistance of osteosarcoma cells were investigated by microarray analysis. Numerous genes determined as differentially expressed in VCR-resistant osteosarcoma cells may also be associated with VCR resistance in the present study, such as MDR1 (11), which was upregulated in MG63/VCR cells. Previous studies have indicated that MDR1 serves a key role in the proliferation and survival of epithelial and malignant cells during tumorigenesis, as well as in acquired drug resistance (15,16).…”
Section: Discussionsupporting
confidence: 50%
“…The human VCR-resistant osteosarcoma cell line MG63/VCR and its parental cell line MG63 were obtained from the Scientific Research Center, China-Japan Union Hospital of Jilin University (Jilin, China) (11). The cells were cultured in high-glucose Dulbecco's modified Eagle's medium (H-DMEM; Invitrogen, Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10% fetal bovine serum (FBS; HyClone; GE Healthcare Life Sciences, Logan, UT, USA) in a humidified atmosphere with 5% CO 2 at 37°C; three biological replicates were conducted using the MG63 and MG63/VCR cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B ) ( 1 , 21 ). These drugs included an anti-microtubule agent (PTX), an antimetabolite (MTX) and two topoisomerase II inhibitors (DOX and THP) ( 22 ). Notably, the mRNA and protein expression levels of LIMK1 and MDR1/P-gp were higher in MG63/VCR cells than in MG63 cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are two isoforms of topoisomerase II: Topoisomerase IIα and topoisomerase IIβ [90,91]. OS cell lines (143B, MG63, and HOS) showed a reduction of topoisomerase II expression in DOX-resistant cells compared to sensitive cells [85,92,93], suggesting that a decrease of DOX target is one of the mechanisms of drug resistance.…”
Section: Alterations In the Structure Or Expression Of The Target Enzymementioning
confidence: 99%